Estimating farmers’ willingness to pay for photovoltaic industry to improve agricultural green resources and environment - Li, Jinyang; Khan, Arshad Ahmad; Khan, Sufyan Ullah; Ali, Muhammad Abu Sufyan; Luo, Jianchao (Frontiers in Environmental Science, 2022)
Based on consideration of the level of regional radiation effect of photovoltaic industry, this research selected four main regions as case sites in Pingluo County, Ningxia province. The study used the double-bounded dichotomous CVM model, and C-optimal design to revise the bidding value of the payment scheme that reduced the WTP range error. Five independent sub-sample questionnaires including 7 bidding value payment schemes along with 4 internal range tests and 6 external range tests were designed. The results showed that the comparison of the WTP for the improvement of agricultural resources and environment among different independent sub-samples in the same region has passed the external quantitative scope test, indicating that the questionnaire design, survey implementation and WTP estimation results of the double-bounded dichotomous CVM in this study were reliable. Saturation degree, diminishing marginal utility and substitution effect are the main influencing factors of low marginal WTP added value and embedding effect. When the quantity range changes, the utility of respondents tends to saturate and marginal utility rapidly decreases. Influenced by the above factors, the sum of the independent estimates of the respondents on the WTP for the improvement of agricultural green resources and environment of the photovoltaic industry in the four research areas is 3.04 times of the average value of the overall estimates of the four areas. In order to obtain and maintain the local photovoltaic industry for agricultural production resources and environment improvement, the average WTP of each respondent was 99.80 yuan per year.